PERFORMANCE REQUIRED OF FUTURE INFORMATION PROFESSIONALS - Agha, Syed Salim (Malaysian Journal of Library and Information Science, 1997)
The digital revolution has brought with it unprecedented changes. These changes have affected all concerned in the value-added information chain including librarians and other information professionals. Areas of focus, on which the librarians should pay attention to, have been outlined. Future activities of information professionals, in keeping with computer-mediated communication environments have been projected. Some aspects of expected performance of information professionals have been indicated.